Abordagem Multicritério Para A Classificação De Áreas Para Doenças Transmitidas Pelo Mosquito Aedes Aegypti - Aguiar, Emerson Santos [UNIFESP] (2018)
In face the current scenario of outbreaks and epidemics of Zika, Chikungunya and Dengueâs outlined by the spread of these viruses around the world, recognizing the epidemic at the outset, through risk or vulnerability assessment, is essential for the planning of mitigation and control actions over the impact of these diseases on society. As follows, the objective of this work was to assist the epidemiological surveillance of diseases associated with the Aedes aegypti mosquito in society by constructing maps of vulnerability from a multicriteria spatial decision model. Initially, a bibliographic study was designed to identify the determinants of the vulnerability of areas to Zika, Chikungunya and Dengue; these factors were used as a basis for structuring the criteria used in the multicriteria model. Given the importance that the evaluated areas presented satisfactory and balanced performances in most of the criteria, the use of the non-compensatory multicriteria method PROMETHEE II was considered to construct the map of vulnerability. The proposed approach was applied in a case study to classify neighborhoods of a city in northeastern Brazil. The response provided by the approach was presented spatially on thematic maps created in a geographic information system. The results suggest that the proposed model is useful as a decision support tool in the epidemiological surveillance of Aedes aegypti-related diseases, allowing a definition of the vulnerability of areas related to Aedes aegypti, a more effective definition of the vulnerability of areas to diseases transmitted by Aedes aegypti, as well as allowing assistance in a more efficient decision-making process on disease mitigation and control measures. The model supports the process from the investigation of the factors determining the vulnerability of the areas, assists in the evaluation of the health conditions of the population through the performance of the districts, both individually and in an aggregated way, and, finally, helps in the design and evaluation of actions to prevent and control diseases.